CYP2R1 Mutations Impair Generation of 25-hydroxyvitamin D and Cause an Atypical Form of Vitamin D Deficiency - Thacher, Tom D.; Fischer, Philip R.; Singh, Ravinder J.; Roizen, Jeffrey; Levine, Michael A. (The journal of clinical endocrinology and metabolism, 2015)
Context:Production of the active vitamin D hormone 1,25-dihydroxyvitamin D requires hepatic 25-hydroxylation of vitamin D. The CYP2R1 gene encodes the principal vitamin D 25-hydroxylase in humans.Objective:This study aimed to determine the prevalence of CYP2R1 mutations in Nigerian children with familial rickets and vitamin D deficiency and assess the functional effect on 25-hydroxylase activity.Design and Participants:We sequenced the CYP2R1 gene in subjects with sporadic rickets and affected subjects from families in which more than one member had rickets.Main Outcome Measures:Function of mutant CYP2R1 genes as assessed in vivo by serum 25-hydroxyvitamin D values after administration of vitamin D and in vitro by analysis of mutant forms of the CYP2R1.Results: CYP2R1 sequences were normal in 27 children with sporadic rickets, but missense mutations were identified in affected members of 2 of 12 families, a previously identified L99P, and a novel K242N. In silico analyses predicted that both substitutions would have deleterious effects on the variant proteins, and in vitro studies showed that K242N and L99P had markedly reduced or complete loss of 25-hydroxylase activity, respectively. Heterozygous subjects were less affected than homozygous subjects, and oral administration of vitamin D led to significantly lower increases in serum 25-hydroxyvitamin D in heterozygous than in control subjects, whereas homozygous subjects showed negligible increases.Conclusion:These studies confirm that CYP2R1 is the principal 25-hydroxylase in humans and demonstrate that CYP2R1 alleles have dosage-dependent effects on vitamin D homeostasis. CYP2R1 mutations cause a novel form of genetic vitamin D deficiency with semidominant inheritance.